The utility of trauma history and current psychopathology in predicting preventive health behaviors - Sheela Raja; Emily P. Rabinowitz; Steve Gonzalez; Megan Lee; Shivali Padmani; Memoona Hasnain (Scientific Reports)
Abstract This pilot study explored the relationship between self-reported trauma exposure, psychopathology, and coping strategies and preventive health behaviors (PHBs) and self-rated health (SRH) in a sample of clinic patients in a large, urban health system. Results indicated that trauma exposure explained only a small portion of the variance in PHBs and SRH. Higher trauma exposure was not associated with lower PHB engagement, suggesting that trauma’s impact on health behaviors may be more nuanced. Specifically, current self-reported psychopathology, including depression, anxiety, and PTSD, was negatively correlated with PHB engagement, and coping strategies accounted for additional variance in PHBs beyond trauma and psychopathology. SRH was significantly influenced by trauma exposure, especially in the presence of psychological distress, but no significant relationship was found between SRH and coping strategies. These results underscore the importance of screening for current psychopathology and coping strategies in healthcare settings, rather than solely focusing on trauma history. Although trauma informed healthcare interventions may focus on screening for trauma, our results suggest that programs should prioritize mental health screening and coping assessment to better address individuals’ health risks and promote resilience. Future research should investigate how various types of trauma may differentially impact patients’ health behaviors and coping.